Teacher reports of peer aggression in preschool: its relationship to DSM-IV externalizing symptoms - Canals, Josepa; Mitjavila, Mercé; Domènech-llaberia, Edelmira; Claustre Jané, M.; Corbella, Teresa; Ballespí, Sergi (The Spanish Journal of Psychology, 2008)
Objective: to establish the prevalence and associations of peer aggression as manifested in preschool children, in community-based populations and to study links with DSM-IV externalizing diagnoses. Method: Subjects were 1,104 children, 3-to-5-year-olds attending rural and urban pre-schools classes. Teachers completed the Peer Conflict Scale (PCS) to inform about direct physical and verbal aggression, object aggression and symbolic aggression and the questionnaire on psychopathology ECI-4. Results: 6.6% (n = 73) had at least one positive item on the PCS. This percentage dropped to 2.6% (n = 29) if we take into account a minimum of three positive items. Physical direct aggression was the more prevalent type of aggressive behavior, followed by verbal aggression, object aggression and symbolic aggression. Significant differences by gender and age were found. Peer aggression was associated with male gender from three years of age. Physical, object and verbal aggressive behavior was linked with externalizing disorders. This association was very strong with oppositional disorder. Conclusions: The present research with a Spanish population confirms the existence of peer aggression in preschoolers and the gender differences. Our chief contribution is about the age of emergence of sex differences and gender differences in different types of peer aggression.